Is higher lymphocyte count a potential strategy for preventing chronic kidney disease in patients receiving long-term dasatinib treatment? - Hirokazu Nakayama; Hiromitsu Iizuka; Toshiaki Kato; Kensuke Usuki (BMC, 2023)
Abstract Background Dasatinib, which is used to treat treating chronic myeloid leukemia, induces increases in blood lymphocytes during the treatment. In addition, neutrophil-lymphocyte count ratio (NLR) is associated with the related to development of chronic kidney disease (CKD). However, it has not been reported whether development of CKD during long-term dasatinib treatment is related to lymphocyte count or NLR. This study aimed to reveal the relationship between CKD and lymphocyte count or NLR during long-term dasatinib treatment. Methods A retrospective study was conducted in patients treated with dasatinib for 6 months or longer. Risk factors for CKD development were explored using multivariate analysis. Changes in maximal lymphocyte count and NLR over time were examined separately. Results A total of 33 patients in CKD group (n = 8) and No CKD group (n = 25) who received dasatinib were enrolled. In univariate analysis, significant differences between the groups were observed in maximal lymphocyte count, lymphocytosis, age, and estimated glomerular filtration rate at baseline. As the factor independently associated with the development of CKD, maximal lymphocyte count (odds ratio 0.999, 95% confidence interval: 0.999-1.000, p = 0.033) was identified. In this analysis, age had borderline significance (odds ratio 1.073, 95% CI: 0.999-1.153, p = 0.054)]. After 6 months of dasatinib therapy, lymphocyte count was significantly lower in CKD group [median (range), 2184 (878‒3444)/μL] than in the No CKD group [3501 (966‒7888)/μL] (p = 0.020). However, no significant difference in lymphocyte count was observed between the groups at the last follow-up. During the study period, the median NLR in the No CKD group fluctuated between 1.11 and 1.42, and median NLR in CKD group was increased from 1.13 to 2.24 between after 6 months of dasatinib therapy and the last follow-up. Conclusions The development of CKD during dasatinib therapy was associated with lower maximal lymphocyte counts. In contrast, the higher levels of lymphocytes induced during dasatinib treatment may prevent CKD progression.